Raw Multi-Channel Seismic Shot Data from the Antarctic Peninsula acquired during R/V Maurice Ewing expedition EW9101 (1991) ... - Mutter, John; Austin, James; Shipley, Thomas; Dalziel, Ian (Interdisciplinary Earth Data Alliance (IEDA), 2014)
This data set was acquired with the LDEO Multi-Channel Seismic system during R/V Maurice Ewing expedition EW9101 conducted in 1991 (Chief Scientist: Dr. James Austin; Investigator: Dr. John Mutter). These data files are of SEGY format and include Multi-Channel Reflection Seismic shot data that have not been processed. Data were acquired as part of the projects: The Bransfield Strait-South Shetland Islands/Trench: Structural and Stratigraphic Evolution of a Linked(?) Back-arc/Fore-arc System and The Pacific Margin of the Antarctic Peninsula: A Marine Geophysical Study of the Tectonic Evolution of Andean-Type Orogens, and funding was provided by NSF grants: DPP89-17332 and OCE94-18135. These data are cited by Barker and Austin, 1998, Barker and Austin, 1994, and Barker, 1997. ...